Radiochemical Study of Biopolymers Sorption on Hydrophobic Surfaces - Chernysheva, M.G.; Badun, G.A. (Хімія, фізика та технологія поверхні, 2010)
The behavior of globular proteins (lysozyme, human serum albumin) and humic acids of coal (Powhumus) in aqueous/oil and aqueous/graphene systems was studied by means of tritium tracer. Tritium labeled biomolecules were obtained by tritium thermal activation method. Adsorption isotherms were obtained by liquid scintillation spectrometry of tritium either in traditional performance or in scintillation phase technique